KNOWLEDGE, ATTITUDE AND PRACTICE AMONG HEALTHCARE PROFESSIONALS TOWARDS ADR REPORTING IN ABBOTTABAD PAKISTAN (International Journal of Pharmacy & Integrated Health Sciences)
Background: Healthcare professionals can play an important role in reporting adverse drug reactions as it is a global health problem and required to be addressed.